A highly sensitive hyperbranched Au plasmonic blackbody immunochromatographic assay for detection of leucomalachite green in fish and shrimp - Teepoo, Siriwan; Jantra, Jongjit; Panapong, Khaunnapa; Ajayi, David Taiwo (My University, 2024)
A novel immunochromatographic assay (ICA) based on hyperbranched Au plasmonic blackbodies (AuPBs) with a smartphone readout was fabricated for the detection of leucomalachite green (LMG) in fish and shrimp products. The ICA was carried out in a competitive immunoassay format with AuPBs as labels. The developed AuPBs-ICA allowed for the LMG detection with a low detection limit (0.15 μg L−1) within 5 min by the smartphone reader. With the label-AuPBs ICA, the color intensity response was linearly related to the concentrations of the LMG (0.2 −1.7 μg L−1). The test line signal could be clearly distinguished at a 1.7 μg L−1 LMG as a cut-off level by the naked eye, which is lower than the conventional colloidal gold nanoparticle (2 μg L−1) and star-shaped nanoparticles (1.9 μg L−1) labeling. LMG contamination in samples was determined with the proposed AuPBs-ICA and the enzyme-linked immunosorbent (ELISA). The AuPBs-ICA results showed good agreement with those from the ELISA. The proposed AuPBs-ICA has the potential to be used as a rapid, sensitive, and simple device for the analysis of LMG residues in fish and shrimp samples.
Keywords: Fish; Hyperbranched Au plasmonic blackbody; Immunochromatographic assay; Leucomalachite green; Shrimp